Virologic and immunologic response to HAART, by age and regimen class. - Althoff, Keri N; Justice, Amy C; Gange, Stephen J; Deeks, Steven G; Saag, Michael S; Silverberg, Michael J; Gill, M John; Lau, Bryan; Napravnik, Sonia; Tedaldi, Ellen; Klein, Marina B; Gebo, Kelly A (AIDS (London, England), 2010)
To determine the impact of age and initial HAART regimen class on virologic and immunologic response within 24 months after initiation.
Keywords: Adolescent; Adult; Age Distribution; Antiretroviral Therapy, Highly Active; CD4 Lymphocyte Count; Female; HIV Infections; HIV-1; Humans; Logistic Models; Male; Middle Aged; RNA, Viral; Viral Load; Young Adult